Indonesia Teachers’ Citizenship Behavior: The Role of Perceived Organizational Support, Emotional Intelligence and Job Satisfaction - Sri Handari Wahyuningsih; Hijriyatur Rizky Nurlaeli (CV. Ulil Albab Corp, 2024)
An essential part of learning success is played by teachers. Accelerating educational performance is a great objective, but it requires teachers to have positive attitudes and behaviors. By examining the antecedents of perceived organizational support, emotional intelligence, and positive attitudes toward job satisfaction as mediators, this study attempts to analyze extra role behavior, specifically organizational citizenship conduct. Teachers who answered all 35 questions completely, describing the four variable constructions under study, were identified as respondents in this study. Path analysis using SPSS version 22 and the Sobel test is the analysis method used to assess the given hypothesis. The study's findings suggest that perceived organizational support and emotional support can enhance organizational citizenship behavior. These findings have implications for both the necessity of developing high-quality organizational support to promote good attitudes and conduct in educational settings and the necessity of raising emotional intelligence as a crucial skill for all teachers doing their jobs.